The Price of Poverty: Policy Implications of the Unequal Effects of Monetary Sanctions on the Poor. (February 2021) - Slavinski, Ilya; Spencer-Suarez, Kimberly
Over the last several decades, with the rise of mass incarceration in the United States and its steep costs, governments at the federal, state, and local levels have dramatically ramped up monetary punishment. Monetary sanctions are now the most common type of criminal penalty in the United States. The growth of fines, fees, and other legal financial obligations (LFOs), and the ensuing legal debt, reflect a shifting of the system's costs onto its primarily low-income and indigent subjects. This study provides an exploration of previously underexamined ways in which monetary sanctions impose distinct burdens on the poor. Interviews with 121 defendants in Texas and New York, along with courtroom observations, demonstrate that criminal legal debt is particularly challenging for people with low incomes in three meaningful ways. First, systems set up to handle indigency claims do not adequately address the needs or complex individual circumstances of those who simply do not have the ability to pay. Oftentimes, alternatives are unavailable or statutorily prohibited. Second, the lack of alternatives to payment lead to compromising situations, which then compel indigent defendants to make difficult choices about how to allocate scant resources. Finally, being encumbered with fines and fees and participating in alternatives like community service comes with taxing time requirements that can prove uniquely challenging for those who are poor. These three findings lead us to propose a series of policy recommendations revolving around three key themes: (a) enhancement of indigency procedures, (b) equity in monetary sanctions, and (c) alleviating burdens by improving accessibility.